Intra‐articular injection of orthobiologics in patients undergoing high tibial osteotomy for knee osteoarthritis is safe and effective – a systematic review - Brjan Kaiji Betzler; Aiman Haziq Bin Muhammad Ridzwan Chew; Hamid Rahmatullah Bin Abd Razak (Journal of Experimental Orthopaedics, 2021)
Abstract Purpose To qualitatively evaluate the current evidence reporting outcomes of intra‐articular injection of orthobiologics in patients undergoing high tibial osteotomy (HTO) for osteoarthritis of the knee. Methods A systematic search methodology of the PUBMED, EMBASE, and CINAHL databases was conducted in July 2021. The search workflow was in adherence to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA). The following inclusion criteria were adopted: clinical trials of any level of evidence, reporting outcomes following intra‐articular injection of orthobiologics during high tibial osteotomy for knee osteoarthritis, with a minimum number of 10 patients treated. Duplicate data, studies on implanted orthobiologics and articles not written in English were excluded from this review. Results Eight studies were included in this review, with a total of 585 patients. Outcomes were discussed based on the types of orthobiologics used: (i) Platelet‐Rich Plasma (PRP), (ii) Bone Marrow Aspirate Concentrate (BMAC), and (iii) Injected Mesenchymal Stem Cells (MSCs). Two studies utilised PRP, 4 studies utilised BMAC and 4 studies utilised injected MSCs.. Three studies provided Level II evidence and five studies provided Level III evidence. Statistically significant improvements in outcomes were documented in multiple trials, with few patients experiencing adverse events. Conclusion Intra‐articular injection of orthobiologics in patients undergoing HTO is safe and effective with good outcomes reported. Due to the lack of high‐level evidence, further research is required before this can be considered standard of care. Level of evidence III